Enhancing early intervention services for children with special needs in the middle east: A Turkish initiative - (:unkn) unknown (Anadolu Universitesi, 2014)
At a conference hosted by the Association of Turkish Educators entitled "Early Intervention from Interdisciplinary Perspectives," discussion focused on enhancing and designing best practices in early intervention special education for the Turkish region. Governmental representatives, post-secondary educators, educational specialists, teachers, administrators, parents and concerned citizens grappled with past, current and future educational practices in an attempt to enhance educational services for students with special needs in the Turkish region. Five critical discussion themes spotlighted assessment and diagnosis, early intervention, educational strategies, professional development and community awareness. Keynote speakers were educational specialists with expertise in best practices from the United States and Europe. As a result of the presentations and discussions, recommendations were compiled for implementation.
Keywords: Developmental disabilities; Early intervention; Special education